Multiplex analysis of plasma cytokines/chemokines showing different immune responses in active TB patients, latent TB infection and healthy participants. (December 2017) - Yao, Xiangyang; Liu, Yongliang; Liu, Yang; Liu, Wei; Ye, Zhizhong; Zheng, Chao; Ge, Shengxiang
Abstract: Interferon gamma release assays (IGRAs) have been widely used to diagnose Mycobacterium tuberculosis (MTB) infection. However, IGRAs cannot discriminate between active TB patients and latent TB infection (LTBI), and the sensitivity of IGRAs for MTB infection is suboptimal. Here, we analyzed cytokines/chemokines in MTB antigen-stimulated and -unstimulated plasma samples to identify host biomarkers that are associated with active TB and MTB infection. Active TB patients, subjects with LTBI and healthy participants were recruited. Seventy-one soluble cytokines and chemokines were tested using Luminex liquid array-based multiplexed immunoassays. For the 71 examined factors, our results indicated that the unstimulated levels of IL-8Nil, IP-10Nil, MIP-1aNil, and sIL-2RaNil and the antigen stimulated levels of IL-8(Ag-Nil), VEGF(Ag-Nil), and MCP-3(Ag-Nil) were potential biomarkers for differentiating between active TB and LTBI, with AUCs of 0.8, 0.86, 0.755, 0.845, 0.825, 0.812 and 0.75, respectively. The G-CSF(Ag-Nil), GM-CSF(Ag-Nil), IL-1a(Ag-Nil), IL-2(Ag-Nil), IP-10(Ag-Nil), BCA-1(Ag-Nil) and Eotaxin-1(Ag-Nil) responses were significantly higher in patients with active TB and LTBI compared with healthy participants (p < 0.05), with AUCs of 0.922, 0.902, 0.908, 1.0, 0.937, 0.919 and 0.935, respectively. Our preliminary data suggest that unstimulated or stimulated levels of cytokines and chemokines could be used as host biomarkers for diagnosing active TB as well as additional biomarkers, except IFN-γ, for MTB infection.